The Existence of Women Activists in Aceh Politics After the Helsinki MOU : Eksistensi Aktivis Perempuan dalam Politik Aceh Pasca MOU Helsinki - Wahyuni, Hamdina (The Department of Islamic History and Culture in cooperation with the Center for Islamic History and Culture in Aceh and Malay World Studies (PUSAKA), Universitas Islam Negeri Ar-Raniry Banda Aceh, Aceh, Indonesia, 2024)
The existence of women can be seen in the participation form in public dimension and politics is like the efforts to achieve peace in Aceh. The role of women activists not only in the times of conflict, but also in peacetime is a reality, however it still less exposed. Undoubtedly that the Acehnese women activist from time to time have played a big role. But in fact there are still less of Acehnese women that have opportunity to be active role in the government. For the politics only still have limited space to move. As well as the role in political parties, women only fulfill the political parties quota. This research aims to know the involvement of women activist in politics of Aceh and to know the role of women activist pasca MOU Helsinki in relations to the rights of engagement in Aceh politics. The result of research shows that the existence of Acehnese women in times of conflict until peacetime, really concentrates on the issues that related to women and fighting for the women’s right. Afterwards the role of Acehnese women activist is not only limited in the role of social program of humanity, but it already leads to the role of practical politics, hopes to sit down in the parlement to be born the policy and the regulation that set the protection of women rights and the women empowerment from every sectors. It is reasonable that Acehnese women put hopes on politics to change the fate of Acehnese women civilization now and in the future.